MECHANISMS IN ENDOCRINOLOGY: An update in the genetic aetiologies of combined pituitary hormone deficiency. Issue 6 (June 2016) - Castinetti, Frederic; Reynaud, Rachel; Saveanu, Alexandru; Jullien, Nicolas; Quentien, Marie Helene; Rochette, Claire; Barlier, Anne; Enjalbert, Alain; Brue, Thierry
Abstract : Over the last 5 years, new actors involved in the pathogenesis of combined pituitary hormone deficiency in humans have been reported: they included a member of the immunoglobulin superfamily glycoprotein and ciliary G protein-coupled receptors, as well as new transcription factors and signalling molecules. New modes of inheritance for alterations of genes encoding transcription factors have also been described. Finally, actors known to be involved in a very specific phenotype (hypogonadotroph hypogonadism for instance) have been identified in a wider range of phenotypes. These data thus suggest that new mechanisms could explain the low rate of aetiological identification in this heterogeneous group of diseases. Taking into account the fact that several reviews have been published in recent years on classical aetiologies of CPHD such as mutations of POU1F1 or PROP1, we focused the present overview on the data published in the last 5 years, to provide the reader with an updated review on this rapidly evolving field of knowledge.